2016
DOI: 10.1590/s0100-83582016340300014
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Common Bean Plants to Ethoxysulfuron Herbicide and the Mechanism Involved in the Process

Abstract: -The objectives of this study were to determine the effect of herbicide ethoxysulfuron on the development of commom bean (Phaseolus vulgaris), to evaluate the impact of the herbicide on the crop grain yield and to determine the mechanism of tolerance of common bean to ethoxysulfuron. Field experiments were carried out with several doses of ethoxysulfuron to determine its effect on the grain yield of two varieties of common bean ("IPR Andorinha", "IPR Tangará"). The mechanism of plant tolerance was evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…In cultivated plants, the metabolization of the herbicide molecule by specific enzymes, such as P450 mono-oxygenases and Glutathione-S-Transferase (Werck-Reichhart et al, 2000;Powles and Yu, 2010) stands out. Previous studies have shown that the main mechanism involved in bean tolerance to ethoxysulfuron is the metabolization of the herbicide molecule (Pagnoncelli Jr. et al, 2016). Overall data corroborate the hypothesis that bean cultivars have a differential capacity to metabolize ethoxysulfuron.…”
Section: Resultados and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In cultivated plants, the metabolization of the herbicide molecule by specific enzymes, such as P450 mono-oxygenases and Glutathione-S-Transferase (Werck-Reichhart et al, 2000;Powles and Yu, 2010) stands out. Previous studies have shown that the main mechanism involved in bean tolerance to ethoxysulfuron is the metabolization of the herbicide molecule (Pagnoncelli Jr. et al, 2016). Overall data corroborate the hypothesis that bean cultivars have a differential capacity to metabolize ethoxysulfuron.…”
Section: Resultados and Discussionsupporting
confidence: 85%
“…In Brazilian literature, there are few studies that demonstrate the different tolerance of bean cultivars to herbicides, especially ALS inhibiting herbicides. Recent studies have demonstrated that ethoxysulfuron is selective to bean crops (Assis et al, 2014;Pagnoncelli Jr. et al, 2016). However, as it happens to other cultivated species, it is believed that there is a different tolerance of bean cultivars to the herbicide.…”
Section: Introductionmentioning
confidence: 99%
“…The effect is reported mainly when herbicides inhibiting acetolactate synthase (ALS), some of photosystem II (PSII; bentazon and propanil), and acetyl CoA carboxylase (ACCase) 3 are combined with insecticides from the organophosphorus and carbamate groups (McRae et al, 1964;Matsunaka, 1968;Campbell and Penner, 1982;Biediger et al, 1992;Baerg et al, 1996;Ahrens and Panara, 1997). Studies have indicated that the combination of the herbicide ethoxysulfuron with organophosphorus insecticides (malathion + chlorpyrifos) increased injuries caused by herbicide on the bean crop when compared to the isolated herbicide application (Pagnoncelli Jr et al, 2016). Similar results have been observed in corn with the combination of nicosulfuron and chlorpyrifos (Silva et al, 2005), as well as in wheat with the application of imazamox and malathion (Rojano-Delgado et al, 2015).…”
mentioning
confidence: 66%
“…Em conjunto, estes dados demonstram que as plantas de feijão possuem alta capacidade de recuperação do efeito do herbicida. Em trabalhos conduzidos avaliando o mecanismo de tolerância das plantas de feijão ao ethoxysulfuron, através do uso de inibidores da metabolização (malathion+chlorpyrifos) e protetor (mefenpyr-diethyl), constatou-se que o principal mecanismo envolvido é a metabolização da molécula do herbicida (Pagnoncelli Jr et al, 2016).…”
Section: Resultsunclassified